Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan: Survey Pada Salah Satu Penyedia Jasa Internet di Kota Bandung - Desi Rismawati; Irena Larashati; Dudung Juhana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
The results of this study were carried out to know the effect of price and service quality on customer satisfaction. The study used a survey approach to internet service customers as many as 100 people in the city of Bandung. Based on research using path analysis, it appears that the price variable has a direct influence of 14.7%. The indirect effect through the service quality variable is 13.1%, the total effect is 27.9%. On the other hand, service quality variables directly influence 32.1%. The indirect effect through the variable price is 13.1%, the total effect is 45.2%. The coefficient of determination (R-square) relationship expressed in the percentage of the contribution of all independent variables price and service quality in determining customer satisfaction variables is 73.1%. In comparison, other factors that affect customer satisfaction not examined shown by the value Є = 0.269 Or 26.9%. The recommendation is that the company should further improve the quality of the internet and other products to improve customer satisfaction.